Phosphorus-containing silane compound, method for producing the same, resin composition and product thereof
By using reactive phospho-containing silane compounds in electronic materials, the existing materials have been solved in terms of thermal expansion, adhesion, dielectric properties and flame retardancy, and higher integration, lower power consumption and higher performance are achieved.
Patent Information
- Application Number
- CN202111233788.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-10-22
AI Technical Summary
Existing electronic materials have challenges in high integration, low power consumption and high performance, especially in terms of thermal expansion, adhesion, copper foil tension, dielectric properties and flame retardancy.
A reactive phospho-containing silane compound having a SiR1(R2)n(R3)3-n structure was prepared by reacting phenyltrivinylsilane with 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide or diphenylphosphine oxygen at 160°C to 200°C. This compound is used in resin compositions and is used to make semi-cured sheets, resin films, laminated plates and printed circuit boards.
This technical method significantly improves the Z-axis thermal expansion rate, copper foil tension, intra-board fluid glue, edge stripes, dielectric constant, dielectric loss and flame retardancy, etc. It can meet a number of technical requirements at the same time and improve the reliability and performance of electronic materials.
Smart Images

Figure CN116003468B_ABST
Abstract
Description
Technical Field
[0001] The present invention mainly relates to a phosphorus-containing silane compound, a method for producing the same, a resin composition and articles made therefrom, and in particular to a reactive phosphorus-containing silane compound that can be applied to prepregs, resin films, laminates (such as copper foil substrates) and printed circuit boards, a method for producing the same, a resin composition and articles made therefrom. Background Art
[0002] In recent years, electronic technology is developing towards higher integration, lower power consumption and higher performance, which puts higher requirements on high-performance electronic materials.
[0003] With the high integration of electronic components per unit area, in order to improve the interconnection and installation reliability of electronic components, the material is not only required to have a lower thermal expansion coefficient to ensure that the material has a higher dimensional stability to facilitate smooth positioning during the subsequent printed circuit board processing, but also requires the material to have sufficient adhesion to ensure that the material and the metal circuit can be tightly bonded to prevent failures caused by circuit falling.
[0004] Therefore, how to reduce the thermal expansion coefficient of the insulation layer while taking into account other properties, especially the copper foil tensile strength, dielectric properties, flame retardancy, etc., has become an urgent problem to be solved in this field. Summary of the invention
[0005] In view of the problems encountered in the prior art, especially the inability of existing materials to meet one or more of the above technical requirements, the main purpose of the present invention is to provide a phosphorus-containing silane compound and a preparation method thereof that can overcome at least one of the above technical problems. In addition, the present invention also provides a resin composition that can overcome at least one of the above technical problems, and an article made using the resin composition.
[0006] On the other hand, in order to improve the defects of the prior art, especially the fact that the existing flame retardant materials may affect or deteriorate other properties of the insulating materials or resin compositions while providing flame retardancy to the insulating materials or resin compositions, such as the occurrence of board edge stripes or too low glue flow in the board, the present invention provides a reactive phosphorus-containing silane compound, which can be used in a resin composition to make semi-cured sheets, resin films, laminates and printed circuit boards and other items, so that the items are improved in one or more aspects such as Z-axis thermal expansion coefficient, copper foil tensile force, glue flow in the board, board edge stripes, dielectric constant, dielectric loss, flame retardancy, etc.
[0007] In one aspect, the present invention provides a phosphorus-containing silane compound having SiR1(R2) n (R3) 3-n structure:
[0008]
[0009] Wherein R1 is phenyl, R2 is vinyl, R3 is independently a structure represented by formula (I) or formula (II), and n is equal to 1 or 2.
[0010] In one embodiment, the phosphorus-containing silane compound has any one of the structures shown in the following formula (III) to formula (VI):
[0011]
[0012] On the other hand, the present invention provides a method for producing a phosphorus-containing silane compound, comprising the step of reacting phenyltrivinylsilane with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, DOPO) or diphenylphosphine oxide (diphenylphosphine oxide, DPPO) at a temperature of 160° C. to 200° C., wherein the temperature of 160° C. to 200° C. is the temperature reached by phenyltrivinylsilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide after melting under heating.
[0013] In one embodiment, no solvent and no initiator are added to the reaction of phenyltrivinylsilane with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide.
[0014] In one embodiment, the molar ratio of phenyltrivinylsilane to the reactive functional groups of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide is between 3:1 and 3:2.
[0015] In another aspect, the present invention provides a resin composition comprising the phosphorus-containing silane compound and a resin additive.
[0016] In one embodiment, the resin additive includes vinyl resin, styrene maleic anhydride resin, epoxy resin, phenol resin, benzoxazine resin, cyanate resin, polyester resin, polyamide resin, polyimide resin or a combination thereof.
[0017] In one embodiment, the vinyl-containing resin includes a vinyl-containing polyphenylene ether resin, a maleimide resin, a maleimide triazine resin, a polyolefin resin, styrene, divinylbenzene, di(vinylbenzyl)ether, 1,2,4-trivinylcyclohexane, di(vinylphenyl)ethane, di(vinylphenyl)hexane, bisvinylphenyl dimethylene ether, bisvinylphenyl dimethylene benzene, triallyl isocyanurate, triallyl cyanurate, a prepolymer of any of the foregoing ingredients, or a combination thereof.
[0018] In one embodiment, the vinyl-containing polyphenylene ether resin includes a terminal vinyl benzyl polyphenylene ether resin, a terminal methacrylate polyphenylene ether resin, or a combination thereof.
[0019] In one embodiment, the terminal vinyl benzyl polyphenylene ether resin and the terminal methacrylate polyphenylene ether resin respectively comprise structures represented by formula (VII) and formula (VIII):
[0020]
[0021] Among them, R1 to R 14 Each is independently H or -CH3, W1 and W2 are each independently a C1 to C3 divalent aliphatic group;
[0022] b1 is an integer from 0 to 8;
[0023] Q1 includes any one or a combination of the structures shown in formula (B-1) to formula (B-3):
[0024]
[0025] Y1 and Y2 each independently comprise a structure represented by formula (B-4):
[0026]
[0027] Among them, R 15 To R 30 Each is independently H or -CH3; m1 and n1 are each independently an integer from 1 to 30; and A1 is selected from a covalent bond, -CH2-, -CH(CH3)-, -C(CH3)2-, -O-, -S-, -SO2- or a carbonyl group.
[0028] In one embodiment, the maleimide resin includes 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide oligomer, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, 2,3-dimethylbenzene maleimide, 2,6-dimethylbenzene maleimide, N-phenyl maleimide, a maleimide resin containing an aliphatic long chain structure, or a combination thereof.
[0029] In one embodiment, compared to 100 parts by weight of the vinyl-containing polyphenylene ether resin, in the resin composition, the content of the maleimide resin is 10 parts by weight to 60 parts by weight, and the content of the phosphorus-containing silane compound is 30 parts by weight to 70 parts by weight.
[0030] In one embodiment, the resin composition further comprises an amine curing agent, a flame retardant, an inorganic filler, a curing accelerator, an inhibitor, a dye, a solvent, a toughening agent, a silane coupling agent or a combination thereof as needed.
[0031] In another aspect, the present invention provides an article made of the aforementioned resin composition, including a prepreg, a resin film, a laminate or a printed circuit board.
[0032] In one embodiment, the aforementioned article has one, more or all of the following characteristics:
[0033] The Z-axis thermal expansion rate measured as described in IPC-TM-650 2.4.24.5 is less than or equal to 2.60%;
[0034] The copper foil tensile force measured by the method described in IPC-TM-650 2.4.8 is greater than or equal to 3.30 lb / in;
[0035] The amount of glue flow in the article (e.g., the sample of glue flow in the board) after lamination is greater than or equal to 5.0 mm;
[0036] The surface of the article (e.g., the substrate not containing copper) does not contain board edge stripes upon visual observation;
[0037] The dielectric constant measured at a frequency of 10 GHz with reference to the method described in JIS C2565 is less than or equal to 3.65;
[0038] The dielectric loss measured at a frequency of 10 GHz by the method described in reference to JIS C2565 is less than or equal to 0.0053; and
[0039] The flame retardancy measured by the method described in reference to UL 94 specification was V-0 grade. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 FTIR spectra of the synthesized compound 1 and the raw materials phenyltrivinylsilane and DOPO compounds.
[0041] Figure 2 Schematic diagram of the dendritic distribution on a substrate without copper.
[0042] Figure 3 Schematic diagram of the copper-free substrate without dendritic distribution. DETAILED DESCRIPTION
[0043] In order to enable ordinary technicians in the field to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text have the common meanings understood by ordinary technicians in the field for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0044] As used herein, the terms "include", "comprising", "having", "containing" or any other similar terms are open-ended transitional phrases, which are intended to cover non-exclusive inclusions. For example, a composition or article containing multiple elements is not limited to those listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless otherwise expressly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, as used herein, the interpretation of the terms "include", "comprising", "having", and "containing" should be considered to have specifically disclosed and simultaneously cover closed transitional phrases such as "consisting of..." and "consisting essentially of..."
[0045] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual values within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all sub-ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially the sub-ranges defined by all integer values, and should be deemed to have specifically disclosed individual values such as 1, 2, 3, 4, 5, 6, 7, 8, etc. in the range. Similarly, the range description of "between 1 to 8" should be deemed to have specifically disclosed all ranges such as 1 to 8, 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., and include endpoint values. Unless otherwise specified, the above-mentioned interpretation method is applicable to all contents of the full text of the present invention, regardless of whether the scope is wide or not.
[0046] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether such ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0047] In this document, numerical values should be understood to have the accuracy of the significant digits of the numerical value, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range from 39.50 to 40.49.
[0048] In this article, for the use of Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that subgroups or any individual members of all members in the Markush group or option list can also be used to describe the present invention. For example, if X is described as "selected from the group consisting of X1, X2 and X3", it also means that the claim that X is X1 and the claim that X is X1 and / or X2 and / or X3 have been fully described. Furthermore, for those who use Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that any combination of subgroups or individual members of all members in the Markush group or option list can also be used to describe the present invention. Accordingly, for example, if X is described as "selected from the group consisting of X1, X2 and X3", and Y is described as "selected from the group consisting of Y1, Y2 and Y3", it means that the claim that X is X1 or X2 or X3 and Y is Y1 or Y2 or Y3 has been fully described.
[0049] The following detailed description is merely exemplary in nature and is not intended to limit the present invention and its use. In addition, this document is not limited by any theory described in the foregoing prior art or summary of the invention or in the following detailed description or examples.
[0050] Herein, parts by weight represent parts by weight, which may be any weight unit, such as but not limited to kilograms, grams, pounds, etc. For example, 100 parts by weight of the vinyl-containing polyphenylene ether resin may represent 100 kilograms of the vinyl-containing polyphenylene ether resin or 100 pounds of the vinyl-containing polyphenylene ether resin.
[0051] As used herein, "or a combination thereof" means "or any combination thereof".
[0052] In the present invention, unless otherwise specified, the resin may include a compound and a mixture. A compound includes a monomer or a polymer. A mixture includes two or more compounds, and the mixture may also include a copolymer or other additives, etc., and is not limited thereto.
[0053] For example, a compound refers to a chemical substance formed by two or more elements connected by chemical bonds, which may include monomers, polymers, etc., and is not limited thereto. The compound herein is not limited to a single chemical substance when interpreted, but may also be interpreted as the same type of chemical substance with the same composition or the same properties. In addition, in the present invention, a mixture refers to a combination of two or more compounds. A monomer refers to a compound that can generate a polymer compound through polymerization or prepolymerization. A homopolymer refers to a chemical substance formed by a single compound through polymerization reaction, addition polymerization, and condensation polymerization, and a copolymer refers to a chemical substance formed by two or more compounds through polymerization reaction, addition polymerization, and condensation polymerization, and is not limited thereto. In addition, in the present invention, polymers certainly include oligomers, and are not limited thereto. An oligomer, also known as a low polymer, is a polymer composed of 2 to 20 repeating units, usually a polymer composed of 2 to 5 repeating units.
[0054] In this article, vinyl refers to a compound structure containing an ethylenic carbon-carbon double bond (C=C) functional group. If not otherwise specified, the position of the aforementioned functional group is not particularly limited, for example, it can be located at the end of a long chain structure. Therefore, for example, a vinyl-containing polyphenylene ether resin represents a polyphenylene ether resin containing functional groups such as vinyl, vinylidene, allyl, vinylbenzyl, methacrylate, etc., and is not limited thereto. If not otherwise specified, "vinyl-containing" can be interpreted as a compound structure containing an ethylenic carbon-carbon double bond (C=C) or a functional group derived therefrom, for example, a compound structure containing a vinyl, vinylidene, allyl, vinylbenzyl, or methacrylate functional group, and is not limited thereto.
[0055] As mentioned above, the main purpose of the present invention is to provide a phosphorus-containing silane compound having SiR1(R2) n (R3) 3-n structure:
[0056]
[0057] Wherein R1 is phenyl, R2 is vinyl, R3 is independently a structure represented by formula (I) or formula (II), and n is equal to 1 or 2.
[0058] For example, in one embodiment, n is equal to 1, and R3 is a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide functional group; for example, in one embodiment, n is equal to 1, and both R3 are diphenylphosphine oxide functional groups; for example, in one embodiment, n is equal to 1, and one R3 is a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide functional group, and the other R3 is a diphenylphosphine oxide functional group; for example, in one embodiment, n is equal to 2, and R3 is a 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide functional group; for example, in one embodiment, n is equal to 2, and R3 is a diphenylphosphine oxide functional group.
[0059] For example, in one embodiment, the aforementioned phosphorus-containing silane compound can be used as a reactive flame retardant compound, and has the following advantages: its phosphorus content can be up to 10%, and a small amount of addition can achieve an excellent silicon-phosphorus synergistic flame retardant effect; the molecular polarity is low and the dielectric properties are excellent; it has one or two vinyl groups and can undergo a cross-linking reaction with the resin, thereby preventing the flame retardant from migrating and precipitating in the material; it has a low melting point and is a soft solid at room temperature, and has a low melt viscosity, and adding it to the resin composition can improve the fluidity of the resin and the filling capacity of the resin composition; it has excellent solubility and can be dissolved in solvents such as butanone and toluene at room temperature, while other non-reactive compounds containing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide groups or diphenylphosphine oxide groups cannot be dissolved in solvents such as butanone and toluene, such as the non-reactive phosphorus-containing silane 1 (Formula (XII)) and the non-reactive phosphorus-containing silane 2 (Formula (XIII)) described later.
[0060] For example, in one embodiment, since the phosphorus-containing silane compound described in the present invention does not contain highly polar and strongly hygroscopic groups such as hydroxyl groups, it has excellent dielectric properties and is used in high-speed and high-frequency signal transmission. While providing flame retardancy, it has little effect on or deterioration of the dielectric properties of the material such as Dk and Df.
[0061] For example, in one embodiment, the phosphorus-containing silane compound described in the present invention is compared with the disclosed phosphorus-containing siloxane flame retardants, for example, the phosphorus-containing silane compound described in the present invention is compared with the phosphorus-containing siloxane flame retardants with large molecular weight (usually polymers or mixtures). The phosphorus-containing silane compound described in the present invention has good compatibility with other resins and will not cause problems such as board edge stripes and glue flow inside the board.
[0062] For example, in one embodiment, the phosphorus-containing silane compound of the present invention may have any one of the structures shown in the following formula (III) to formula (VI):
[0063]
[0064] Another main object of the present invention is to provide a method for preparing a phosphorus-containing silane compound, which comprises the step of reacting phenyltrivinylsilane with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide at a temperature of 160° C. to 200° C.
[0065] For example, the phosphorus-containing silane compound can be obtained by reacting phenyltrivinylsilane with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide under heating.
[0066] For example, in one embodiment, the heating time may be between 1 hour and 6 hours, such as between 2 hours and 6 hours, or between 3 hours and 5 hours. The reaction temperature may be between 160°C and 200°C, such as between 170°C and 200°C, or between 180°C and 190°C.
[0067] For example, in one embodiment, during the reaction, no solvent and initiator are added. The addition of an initiator will cause phenyltrivinylsilane to self-polymerize during the reaction, and the phosphorus-containing silane compound cannot be obtained. The addition of a solvent will dilute the concentration of phenyltrivinylsilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide, resulting in a decrease in the yield of the phosphorus-containing silane compound.
[0068] In one embodiment, the amounts of phenyltrivinylsilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide are not particularly limited.
[0069] In one embodiment, the molar ratio of the reactive functional groups of phenyltrivinylsilane to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide is between 3:1 and 3:2 (molar number of reactive functional groups = compound mass / compound molecular weight*number of reactive functional groups in the compound structure). In one embodiment, the molar ratio of the vinyl group in phenyltrivinylsilane to the flame retardant functional group containing phosphorus atoms (i.e., -PH functional group) is between 3:1 and 3:2. In one embodiment, the molar ratio of the vinyl group in phenyltrivinylsilane to the flame retardant functional group containing phosphorus atoms of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 3:1. In one embodiment, the molar ratio of the vinyl group in phenyltrivinylsilane to the flame retardant functional group containing phosphorus atoms of diphenylphosphine oxide is 3:2.
[0070] In one embodiment, the molar ratio of phenyltrivinylsilane to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide is between 1:1 and 1:2.
[0071] For example, in one embodiment, after the reaction is completed, a reactive phosphorus-containing silane compound may be obtained.
[0072] In one embodiment, the preparation methods of the compounds of formula (III), formula (IV), formula (V) and formula (VI) are as follows:
[0073] Preparation Example 1
[0074] Under nitrogen protection, 1.0 mol of phenyltrivinylsilane (containing 3.0 mol of vinyl groups) and 1.0 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (i.e., DOPO compound, containing 1.0 mol of flame retardant functional groups containing phosphorus atoms) were added to a three-necked flask, the temperature was raised to 190° C., and the reaction was stirred for 1 to 6 hours. After the reaction was completed, the temperature was lowered to room temperature to obtain a product, which contained a large amount of synthetic compound 1 (having the structure shown in formula (III)) and a small amount of synthetic compound 3 (having the structure shown in formula (V)), wherein the yield of synthetic compound 1 was above 95%, and the yield of synthetic compound 3 was between 1% and 3%.
[0075] Figure 1 These are the FTIR spectra of the synthetic compound 1 and the raw materials phenyltrivinylsilane and DOPO compound, wherein the top one is the FTIR spectrum of the raw material phenyltrivinylsilane, the middle one is the FTIR spectrum of the raw material DOPO compound, and the bottom one is the FTIR spectrum of the synthetic compound 1.
[0076] In the FTIR spectrum of DOPO compounds, it can be found that 2440cm -1 The 2440cm -1 The PH bond stretching vibration absorption peak at 1600cm disappeared, indicating that the PH bond in the raw material DOPO compound was basically reacted completely; -1 The vinyl peak at 1595 cm -1 P=O peak coverage at 1211cm -1 The PO peak is at 2946 cm, indicating that the double bond of phenyltrivinylsilane has reacted with the DOPO compound and a P=O bond has been generated in the synthesized compound 1; -1 The saturated CH absorption peak at still exists, proving that the DOPO compound and phenyltrivinylsilane have reacted, the double bond of phenyltrivinylsilane has reacted with the DOPO compound, and the DOPO group has been successfully connected.
[0077] Preparation Example 2
[0078] Under nitrogen protection, 1.0 mol of phenyltrivinylsilane (containing 3.0 mol of vinyl groups) and 1.0 mol of diphenylphosphine oxide (i.e., DPPO compound, containing 1.0 mol of flame retardant functional groups containing phosphorus atoms) were added to a three-necked flask, the temperature was raised to 160°C to 190°C, and the reaction was stirred for 1 to 6 hours. After the reaction was completed, the temperature was lowered to room temperature to obtain a product, which contained a large amount of synthetic compound 2 (having the structure shown in formula (IV)) and a small amount of synthetic compound 4 (having the structure shown in formula (VI)), wherein the yield of synthetic compound 2 was above 95%, and the yield of synthetic compound 4 was between 1% and 3%.
[0079] Preparation Example 3
[0080] Under nitrogen protection, 1.0 mol of phenyltrivinylsilane (containing 3.0 mol of vinyl groups) and 2.0 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (i.e., DOPO compound, containing 2.0 mol of flame retardant functional groups containing phosphorus atoms) were added to a three-necked flask, the temperature was raised to 160° C. to 200° C., and the reaction was stirred for 1 to 6 hours. After the reaction was completed, the temperature was lowered to room temperature to obtain a product, which contained a large amount of synthetic compound 3 (having the structure shown in formula (V)) and a small amount of synthetic compound 1 (having the structure shown in formula (III)), wherein the yield of synthetic compound 3 was above 95%, and the yield of synthetic compound 1 was between 1% and 3%.
[0081] Preparation Example 4
[0082] Under nitrogen protection, 1.0 mol of phenyltrivinylsilane (containing 3.0 mol of vinyl groups) and 2.0 mol of diphenylphosphine oxide (i.e., DPPO compound, containing 2.0 mol of flame retardant functional groups containing phosphorus atoms) were added to a three-necked flask, the temperature was raised to 160°C to 200°C, and the reaction was stirred for 1 to 6 hours. After the reaction was completed, the temperature was lowered to room temperature to obtain a product, which contained a large amount of synthetic compound 4 (having the structure shown in formula (VI)) and a small amount of synthetic compound 2 (having the structure shown in formula (IV)), wherein the yield of synthetic compound 4 was above 95%, and the yield of synthetic compound 2 was between 1% and 3%.
[0083] Comparative Preparation Example 1
[0084] Under nitrogen protection, 1.0 mol of phenyltrivinylsilane (containing 3.0 mol of vinyl groups) and 1.0 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (i.e., DOPO compound, containing 1.0 mol of flame retardant functional groups containing phosphorus atoms) were added to a three-necked flask, and 0.5% of a free radical initiator (e.g., 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne peroxide, trade name 25B, purchased from NOF Corporation) based on the total amount of phenyltrivinylsilane and DOPO compound was added, the temperature was raised to 160° C. to 200° C., gelation occurred during the stirring reaction, and the synthetic compound 1 could not be obtained.
[0085] Comparative Preparation Example 2
[0086] Under nitrogen protection, 1.0 mol of phenyltrivinylsilane (containing 3.0 mol of vinyl groups) and 1.0 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (i.e., DOPO compound, containing 1.0 mol of flame retardant functional groups containing phosphorus atoms) were added to a three-necked flask, and 0.5% of a free radical initiator (e.g., 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne peroxide, trade name 25B, purchased from NOF Corporation) based on the total amount of phenyltrivinylsilane and DOPO compound was added, and an appropriate amount of solvent (e.g., toluene, xylene or dimethylacetamide, so that the ideal solid content of the solution is 50 wt% to 70 wt%) was added, the temperature was raised to 160° C. to 200° C., gelation occurred during the stirring reaction, and the synthetic compound 1 could not be obtained.
[0087] Another main object of the present invention is to provide a resin composition, which includes a phosphorus-containing silane compound and a resin additive.
[0088] In the present invention, the phosphorus-containing silane compound can be used as a reactive flame retardant in the resin composition, and the amount of the phosphorus-containing silane compound is not particularly limited, for example, the amount used can be such that the flame retardancy of the resin composition reaches the UL 94 standard V-0 grade.
[0089] Unless otherwise specified, the type of resin additives suitable for the resin composition of the present invention is not particularly limited, and can be various types of resin additives or combinations thereof used in the preparation of prepregs, resin films, laminates or printed circuit boards.
[0090] For example, in one embodiment, the resin additive includes vinyl resin, styrene maleic anhydride resin, epoxy resin, phenol resin, benzoxazine resin, cyanate resin, polyester resin, polyamide resin, polyimide resin or a combination thereof.
[0091] For example, in one embodiment, the resin additive includes a vinyl-containing resin. Examples of the vinyl-containing resin include, but are not limited to, resins containing one or more carbon-carbon double bonds. For example, the vinyl-containing resin includes, but is not limited to, a vinyl-containing polyphenylene ether resin, a maleimide resin, a maleimide triazine resin, a polyolefin resin, styrene, divinylbenzene, bis(vinylbenzyl)ether, 1,2,4-trivinylcyclohexane (1,2,4-trivinylcyclohexane, TVCH), bis(vinylphenyl)ethane (bis(vinylphenyl)ethane, BVPE), di(vinylphenyl)hexane, bisvinylphenyl dimethylene ether, bisvinylphenyl dimethylene benzene, triallyl isocyanurate (TAIC) and / or triallyl cyanurate (TAC). In one embodiment, the vinyl-containing resin includes a prepolymer of any of the foregoing components. In one embodiment, the vinyl-containing resin includes any one of the aforementioned components, a prepolymer of any one of the aforementioned components, or a combination thereof.
[0092] For example, in one embodiment, the vinyl-containing polyphenylene ether resin used in the present invention refers to a polyphenylene ether compound or mixture having an ethylenic carbon-carbon double bond (C=C) or a functional group derived therefrom. Examples of the aforementioned ethylenic carbon-carbon double bond (C=C) or a functional group derived therefrom may include, but are not limited to, functional groups such as vinyl, vinylidene, allyl, vinylbenzyl, methacrylate, etc. contained in the structure. Unless otherwise specified, the position of the aforementioned functional group is not particularly limited, for example, it may be located at the end of a long chain structure. In other words, in the present invention, the vinyl-containing polyphenylene ether resin represents a polyphenylene ether resin containing a reactive vinyl group or a functional group derived therefrom, and examples thereof may include, but are not limited to, a polyphenylene ether resin containing vinyl, vinylidene, allyl, vinylbenzyl or methacrylate.
[0093] For example, in one embodiment, the vinyl-containing polyphenylene ether resin used in the present invention includes terminal vinyl benzyl polyphenylene ether resin, terminal methacrylate polyphenylene ether resin (ie, terminal methacryloyl polyphenylene ether resin), terminal allyl polyphenylene ether resin or a combination thereof.
[0094] For example, the terminal vinylbenzyl polyphenylene ether resin and the terminal methacrylate polyphenylene ether resin respectively include structures represented by formula (VII) and formula (VIII):
[0095]
[0096] Among them, R1 to R14 Each is independently H or -CH3, W1 and W2 are each independently a C1 to C3 divalent aliphatic group;
[0097] b1 is an integer from 0 to 8;
[0098] Q1 includes any one or a combination of the structures shown in formula (B-1) to formula (B-3):
[0099]
[0100] Y1 and Y2 each independently comprise a structure represented by formula (B-4):
[0101]
[0102] Among them, R 15 To R 30 Each is independently H or -CH3; m1 and n1 are each independently an integer from 1 to 30; and A1 is selected from a covalent bond, -CH2-, -CH(CH3)-, -C(CH3)2-, -O-, -S-, -SO2- and a carbonyl group.
[0103] For example, the vinyl-containing polyphenylene ether resin may be SA9000 sold by Sabic, a vinyl benzyl polyphenylene ether resin having a number average molecular weight of about 1200 (e.g., OPE-2st 1200, available from Mitsubishi Gas Chemical Co., Ltd.), a vinyl benzyl polyphenylene ether resin having a number average molecular weight of about 2200 (e.g., OPE-2st 2200, available from Mitsubishi Gas Chemical Co., Ltd.), a vinyl benzyl modified bisphenol A polyphenylene ether resin having a number average molecular weight of about 2400 to 2800, a vinyl chain-extended polyphenylene ether resin having a number average molecular weight of about 2200 to 3000, or a combination thereof. The vinyl chain-extended polyphenylene ether resin may include various types of polyphenylene ether resins disclosed in U.S. Patent Application Publication No. 2016 / 0185904A1, the contents of which are incorporated herein by reference in their entirety.
[0104] For example, in one embodiment, the maleimide resin used in the present invention refers to a compound or mixture having one or more maleimide functional groups in the molecule. Unless otherwise specified, the maleimide resin used in the present invention is not particularly limited and can be any one or more maleimide resins suitable for making prepregs, resin films, laminates or printed circuit boards. Specific examples include, but are not limited to, 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide oligomers, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, 2,3-dimethylbenzene maleimide, 2,6-dimethylbenzene maleimide, N-phenyl maleimide, maleimide resins containing aliphatic long chain structures, or combinations thereof. In addition, unless otherwise specified, the maleimide resin described in the present invention also includes prepolymers of the aforementioned resins, such as prepolymers of diallyl compounds and maleimide resins, prepolymers of diamines and maleimide resins, prepolymers of polyfunctional amines and maleimide resins, or prepolymers of acidic phenol compounds and maleimide resins, etc., but is not limited thereto.
[0105] For example, the maleimide resin may be a maleimide resin produced by Daiwakasei with the trade names of BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-2000, BMI-2300, BMI-3000, BMI-3000H, BMI-4000H, BMI-5000, BMI-5100, BMI-7000 and BMI-7000H, or a maleimide resin produced by KI Chemical with the trade names of BMI-70, BMI-80, or a maleimide resin produced by Sichuan Dongcai Technology Co., Ltd. with the trade names of D928, D930, D932, D934, D936, D937, D938, etc.
[0106] For example, the maleimide resin containing a long chain aliphatic structure may be a maleimide resin produced by a designer molecular company under the trade names of BMI-689, BMI-1400, BMI-1500, BMI-1700, BMI-2500, BMI-3000, BMI-5000 and BMI-6000. For example, the maleimide resin containing a long chain aliphatic structure may have at least one maleimide functional group connected to a substituted or unsubstituted long chain aliphatic group. The long chain aliphatic group may have a carbon number of C5 to C 50 Aliphatic groups, such as carbon number C 10 To C 50 , C20 To C 50 , C 30 To C 50 , C 20 To C 40 or C 30 To C 40 For example, commercially available maleimide resins containing aliphatic long chain structures are as follows:
[0107] BMI-689:
[0108] BMI-1400:
[0109] BMI-1500:
[0110] BMI-1700:
[0111] BMI-2500:
[0112] BMI-3000, BMI-5000, BMI-6000:
[0113]
[0114] For example, in one embodiment, in the styrene maleic anhydride resin used in the present invention, the ratio of styrene (S) to maleic anhydride (MA) may be 1:1, 2:1, 3:1, 4:1, 6:1 or 8:1, such as but not limited to styrene maleic anhydride copolymers sold by Cray Valley under the trade names SMA-1000, SMA-2000, SMA-3000, EF-30, EF-40, EF-60 and EF-80, or styrene maleic anhydride copolymers sold by Polyscope under the trade names C400, C500, C700, C900, etc. In addition, the styrene maleic anhydride resin may also be an esterified styrene maleic anhydride copolymer, such as esterified styrene maleic anhydride copolymers purchased from Cray Valley under the trade names SMA1440, SMA17352, SMA2625, SMA3840 and SMA31890. If not otherwise specified, the above styrene maleic anhydride resins may be added to the resin composition of the present invention independently or in combination.
[0115] For example, in one embodiment, the polyolefin resin of the present invention can be any one or more polyolefin resins suitable for making prepregs, resin films, laminates or printed circuit boards. Specific examples include, but are not limited to, styrene-butadiene-divinylbenzene terpolymers, styrene-butadiene-maleic anhydride terpolymers, styrene-butadiene-styrene terpolymers, vinyl-polybutadiene-urethane oligomers, styrene-butadiene copolymers, hydrogenated styrene-butadiene copolymers, styrene-isoprene copolymers, hydrogenated styrene-isoprene copolymers, polybutadiene, methyl styrene homopolymers, petroleum resins and cyclic olefin copolymers, or a combination thereof.
[0116] For example, in one embodiment, the epoxy resin used in the present invention can be various epoxy resins known in the art, including but not limited to bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AD epoxy resin, novolac epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, multifunctional novolac epoxy resin, dicyclopentadiene (DCPD) epoxy resin, phosphorus-containing epoxy resin, p-xylene epoxy resin, naphthalene epoxy resin (e.g., naphthol epoxy resin), benzofuran epoxy resin, and isocyanate-modified epoxy resin. The novolac epoxy resin may be phenol novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, biphenyl novolac epoxy resin, phenolbenzaldehyde epoxy resin, phenol aralkyl novolac epoxy resin or o-cresol novolac epoxy resin; the phosphorus-containing epoxy resin may be DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) epoxy resin, DOPO-HQ epoxy resin or a combination thereof.The aforementioned DOPO epoxy resin may be selected from one or more of DOPO-containing phenolic novolac epoxy resin, DOPO-containing cresol novolac epoxy resin and DOPO-containing bisphenol-A novolac epoxy resin; the aforementioned DOPO-HQ epoxy resin may be selected from one or more of DOPO-HQ phenolic novolac epoxy resin, DOPO-HQ-containing cresol novolac epoxy resin and DOPO-HQ bisphenol-A novolac epoxy resin.
[0117] For example, in one embodiment, the phenolic resin described in the present invention may be a monofunctional, bifunctional or multifunctional phenolic resin. The type of the above phenolic resin is not particularly limited, and all kinds of phenolic resins currently used in the industry are within the scope of phenolic resins applicable to the present invention. Preferably, the phenolic resin is selected from phenoxy resin, phenolic resin or a combination thereof.
[0118] For example, in one embodiment, the benzoxazine resin of the present invention may be a bisphenol A-type benzoxazine resin, a bisphenol F-type benzoxazine resin, a phenolphthalein-type benzoxazine resin, a dicyclopentadiene benzoxazine resin, or a phosphorus-containing benzoxazine resin, such as LZ-8270 (phenolphthalein-type benzoxazine resin), LZ-8280 (bisphenol F-type benzoxazine resin), LZ-8290 (bisphenol A-type benzoxazine resin) produced by Huntsman, or HFB-2006M produced by Showa Polymer Corporation.
[0119] For example, in one embodiment, the cyanate resin described in the present invention may be various types of cyanate resins known in the art, wherein the cyanate resin includes but is not limited to a cyanate resin having an Ar-OC≡N structure (wherein Ar is an aromatic group, such as benzene, naphthalene or anthracene), a phenol novolac cyanate resin, a bisphenol A cyanate resin, a bisphenol A novolac cyanate resin, a bisphenol F cyanate resin, a bisphenol F novolac cyanate resin, a cyanate resin containing a dicyclopentadiene structure, a cyanate resin containing a naphthalene ring structure, a phenolphthalein cyanate resin or a combination thereof. For example, examples of cyanate resins include, but are not limited to, cyanate resins produced by Lonza under the trade names of Primaset PT-15, PT-30S, PT-60S, BA-200, BA-230S, BA-3000S, BTP-2500, BTP-6020S, DT-4000, DT-7000, ULL950S, HTL-300, CE-320, LVT-50, LeCy, etc.
[0120] For example, in one embodiment, the polyester resin described in the present invention is esterified by an aromatic compound having a dicarboxylic acid group and an aromatic compound having a dihydroxyl group, such as but not limited to HPC-8000, HPC-8150 or HPC-8200 available from Dainippon Ink Chemicals.
[0121] For example, in one embodiment, the polyamide resin described in the present invention may be any type of polyamide resin known in the art, including but not limited to various commercially available polyamide resin products.
[0122] For example, in one embodiment, the polyimide resin described in the present invention may be any type of polyimide resin known in the art, including but not limited to various commercially available polyimide resin products.
[0123] For example, in one embodiment, the maleimide triazine resin of the present invention is not particularly limited, and can be any one or more maleimide triazine resins suitable for prepreg, resin film, laminate or printed circuit board. For example, the maleimide triazine resin can be obtained by polymerizing the cyanate resin and the maleimide resin. The maleimide triazine resin can be, for example but not limited to, obtained by polymerizing bisphenol A cyanate resin and maleimide resin, bisphenol F cyanate resin and maleimide resin, phenol novolac cyanate resin and maleimide resin, or dicyclopentadiene cyanate resin and maleimide resin. For example, the maleimide triazine resin can be obtained by polymerizing cyanate resin and maleimide resin in any molar ratio. For example, the cyanate resin can be 1 to 10 moles relative to 1 mole of maleimide resin. For example, but not limited to, the cyanate resin is present in an amount of 1, 2, 4 or 6 moles relative to 1 mole of the maleimide resin.
[0124] For example, when the phosphorus-containing silane compound of the present invention is used as a reactive flame retardant compound in combination with any one or more of the above-mentioned resin additives, one or more properties of the resin composition can be effectively improved. For example, the phosphorus-containing silane compound of the present invention can show better in-board glue flow, lower thermal expansion coefficient, and no board edge stripes in a system of resins such as maleimide resin (BMI), polyphenylene ether resin (PPO), and polyolefin resin. Preferably, when the phosphorus-containing silane compound of the present invention is used in combination with vinyl-containing resins such as polyphenylene ether resin and maleimide resin, the obtained article can achieve a better balance between excellent comprehensive performance and cost.
[0125] Unless otherwise specified, the ratio between the phosphorus-containing silane compound and the resin additive is not particularly limited.
[0126] For example, in one embodiment, the resin composition includes 100 parts by weight of a vinyl-containing polyphenylene ether resin, 10 parts by weight to 60 parts by weight of a maleimide resin, and 30 parts by weight to 70 parts by weight of a phosphorus-containing silane compound.
[0127] In one embodiment, in addition to the above-mentioned phosphorus-containing silane compound and any one or more resin additives, the resin composition disclosed in the present invention may further include an amine curing agent, a flame retardant, an inorganic filler, a curing accelerator, an inhibitor, a colorant, a solvent, a toughening agent, a silane coupling agent or a combination thereof as needed.
[0128] For example, in one embodiment, the resin composition, in addition to the above-mentioned vinyl polyphenylene ether resin, maleimide resin and phosphorus-containing silane compound, further includes an amine curing agent, a flame retardant, an inorganic filler, a curing accelerator, an inhibitor, a dye, a solvent, a toughening agent, a silane coupling agent or a combination thereof.
[0129] For example, in one embodiment, the amine curing agent of the present invention may be dicyandiamide, diaminodiphenyl sulfone, diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfide or a combination thereof, but is not limited thereto.
[0130] For example, in one embodiment, the flame retardant of the present invention can be any one or more flame retardants suitable for the production of prepregs, resin films, laminates or printed circuit boards. Specific examples include but are not limited to phosphorus-containing flame retardants, such as at least one, a combination of two or more selected from the following groups: ammonium polyphosphate, hydroquinone bis-(diphenylphosphate), bisphenol A bis-(diphenylphosphate), tri(2-carboxyethyl)phosphine (TCEP), tri(chloroisopropyl) phosphate, trimethyl phosphate (TMP), dimethyl methylphosphonate (DMMP), resorcinol bis-(xylyl phosphate) bis (dixylenylphosphate), RDXP, such as PX-200, PX-201, PX-202 and other commercial products), phosphazene (such as SPB-100, SPH-100, SPV-100 and other commercial products), melamine polyphosphate, DOPO and its derivatives or resins, diphenylphosphine oxide (DPPO) and its derivatives or resins, melamine cyanurate, tri-hydroxy ethylisocyanurate, aluminum phosphinate (such as OP-930, OP-935 and other products) or a combination thereof.
[0131] For example, the flame retardant used in the present invention can be a DPPO compound (such as a bis-DPPO compound), a DOPO compound (such as a bis-DOPO compound), a DOPO resin (such as DOPO-HQ, DOPO-NQ, DOPO-PN, DOPO-BPN), a DOPO-bonded epoxy resin, etc., wherein DOPO-PN is a DOPO phenol novolac compound, and DOPO-BPN can be a bisphenol novolac compound such as DOPO-BPAN (DOPO-bisphenol Anovolac), DOPO-BPFN (DOPO-bisphenol F novolac) or DOPO-BPSN (DOPO-bisphenol Snovolac).
[0132] For example, in one embodiment, the inorganic filler described in the present invention can be any one or more fillers suitable for the production of resin films, prepregs, laminates or printed circuit boards, and specific examples include but are not limited to: silicon dioxide (molten, non-molten, porous or hollow), aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, zinc oxide, zirconium oxide, mica, boehmite (AlOOH), calcined talc, talc, silicon nitride or calcined kaolin. In addition, the aforementioned inorganic filler can be spherical, fibrous, plate-like, granular, flaky or needle-like, and can be selectively pretreated with a silane coupling agent.
[0133] In one embodiment, for example, the curing accelerator (including curing initiator) of the present invention may include catalysts such as Lewis base or Lewis acid. Wherein, Lewis base may include one or more of imidazole, boron trifluoride amine complex, ethyltriphenyl phosphonium chloride, 2-methylimidazole (2MI), 2-phenyl-1H-imidazole (2PZ), 2-ethyl-4-methylimidazole (2E4MI), triphenylphosphine (TPP) and 4-dimethylaminopyridine (DMAP). Lewis acid may include metal salt compounds, such as metal salt compounds such as manganese, iron, cobalt, nickel, copper, zinc, such as metal catalysts such as zinc octoate and cobalt octoate. The curing accelerator also includes a curing initiator (i.e., an initiator), such as a peroxide that can generate free radicals. The curing initiator includes, but is not limited to: diisopropyl peroxide, tert-butyl perbenzoate, dibenzoyl peroxide (BPO), 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne (25B), bis(tert-butylperoxyisopropyl)benzene, or a combination thereof.
[0134] In one embodiment, for example, the polymerization inhibitor of the present invention is not particularly limited, for example, it can be various types of polymerization inhibitors known in the art, including but not limited to various commercially available polymerization inhibitor products. For example, the above-mentioned polymerization inhibitor can include but is not limited to 1,1-diphenyl-2-trinitrophenylhydrazine, methacrylonitrile, dithioester, nitrogen oxide stable free radical, triphenylmethyl free radical, metal ion free radical, sulfur free radical, hydroquinone, p-methoxyphenol, p-benzoquinone, phenothiazine, β-phenylnaphthylamine, p-tert-butylcatechol, methylene blue, 4,4'-butylenebis(6-tert-butyl-3-methylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol) or a combination thereof.
[0135] For example, the above-mentioned nitrogen oxide stable free radicals may include but are not limited to nitrogen oxide free radicals from cyclic hydroxylamines such as 2,2,6,6-substituted-1-piperidinyloxy free radicals or 2,2,5,5-substituted-1-pyrrolidinyloxy free radicals. As a substituent, an alkyl group with a carbon number of 4 or less, such as methyl or ethyl, is preferred. As specific nitrogen oxide free radical compounds, 2,2,6,6-tetramethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetraethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetramethyl-4-oxo-1-piperidinyloxy free radicals, 2,2,5,5-tetramethyl-1-pyrrolidinyloxy free radicals, 1,1,3,3-tetramethyl-2-isoindolinyloxy free radicals, N,N-di-tert-butylamineoxy free radicals, etc. can be cited. Stable free radicals such as galvinoxyl free radicals can also be used instead of nitrogen oxide free radicals.
[0136] The polymerization inhibitor applicable to the resin composition of the present invention may also be a product derived from the substitution of hydrogen atoms or atomic groups in the polymerization inhibitor by other atoms or atomic groups, for example, a product derived from the substitution of hydrogen atoms in the polymerization inhibitor by atomic groups such as amino, hydroxyl, ketocarbonyl, etc.
[0137] In one embodiment, for example, the coloring agent suitable for the present invention may include but is not limited to dyes or pigments.
[0138] In one embodiment, for example, the main function of adding a solvent is to change the solid content of the resin composition and adjust the viscosity of the resin composition. For example, the solvent may include, but is not limited to, methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone (also known as methyl ethyl ketone), methyl isobutyl ketone, cyclohexanone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, dimethylformamide, dimethylacetamide, propylene glycol methyl ether, and the like solvents or mixed solvents thereof.
[0139] In one embodiment, for example, the main function of adding a toughening agent is to improve the toughness of the resin composition. The toughening agent may include but is not limited to carboxyl-terminated butadiene acrylonitrile rubber (CTBN), core-shell rubber, and other compounds or combinations thereof.
[0140] In one embodiment, for example, the silane coupling agent used in the present invention may include a silane compound (such as but not limited to a siloxane compound), which can be divided into an amino silane compound, an epoxy silane compound, a vinyl silane compound, an acrylate silane compound, a methacrylate silane compound, a hydroxy silane compound, an isocyanate silane compound, a methacryloxy silane compound, and an acryloxy silane compound according to the type of functional group.
[0141] The resin compositions of the aforementioned embodiments can be made into various articles, such as components suitable for various electronic products, including but not limited to prepregs, resin films, laminates or printed circuit boards.
[0142] For example, the resin composition of each embodiment of the present invention can be made into a semi-cured sheet, which includes a reinforcing material and a layered object disposed on the reinforcing material. The layered object is obtained by heating the aforementioned resin composition at a high temperature to form a semi-cured state (B-stage). The baking temperature for making the semi-cured sheet can be between 100°C and 200°C. The reinforcing material can be any one of a fiber material, a woven fabric, and a non-woven fabric, and the woven fabric preferably includes a glass fiber cloth. The type of glass fiber cloth is not particularly limited, and can be a commercially available glass fiber cloth that can be used for various printed circuit boards, such as E-type glass cloth, D-type glass cloth, S-type glass cloth, T-type glass cloth, L-type glass cloth or Q-type glass cloth, wherein the types of fibers include yarns and rovings, etc., and the form can include open fibers or unopen fibers. The aforementioned non-woven fabric preferably includes a liquid crystal resin non-woven fabric, such as a polyester non-woven fabric, a polyurethane non-woven fabric, etc., and is not limited thereto. The aforementioned woven fabric may also include a liquid crystal resin woven fabric, such as a polyester woven fabric or a polyurethane woven fabric, etc., and is not limited thereto. The reinforcing material can increase the mechanical strength of the prepreg. In a preferred embodiment, the reinforcing material can also be selectively pretreated with a silane coupling agent. The prepreg is subsequently heated and cured (C-stage) to form an insulating layer.
[0143] For example, the resin composition of each embodiment of the present invention can be made into a resin film, which is obtained by semi-curing the aforementioned resin composition after baking and heating. The resin composition can be selectively coated on a polyethylene terephthalate film (PET film), a polyimide film (PI film), a copper foil or a copper foil with adhesive, and then semi-cured after baking and heating, so that the resin composition forms a resin film.
[0144] For example, the resin composition of each embodiment of the present invention can be made into a laminate, which includes two metal foils and an insulating layer disposed between the metal foils. The insulating layer can be obtained by curing (C-stage) the resin composition under high temperature and high pressure conditions, wherein the suitable curing temperature can be between 150°C and 300°C, preferably between 200°C and 280°C, and the curing time is 90 to 180 minutes, preferably 120 to 150 minutes. The insulating layer can be formed by curing (C-stage) the prepreg or resin film. The metal foil can include copper, aluminum, nickel, platinum, silver, gold or their alloys, for example, the metal foil can be copper foil.
[0145] Preferably, the aforementioned laminate is a copper clad laminate (CCL).
[0146] In addition, the aforementioned laminate can be further processed through a circuit manufacturing process to form a circuit board, such as a printed circuit board.
[0147] Preferably, the resin composition or its product provided by the present invention can be improved in one or more aspects such as Z-axis thermal expansion coefficient, copper foil tension, board internal glue flow, board edge stripes, dielectric constant, dielectric loss and flame retardancy.
[0148] For example, the resin composition or its product provided by the present invention may satisfy one, multiple or all of the following characteristics:
[0149] The Z-axis thermal expansion rate measured by the method described in IPC-TM-650 2.4.24.5 is less than or equal to 2.60%, such as between 1.95% and 2.60%;
[0150] The copper foil tensile force measured by the method described in IPC-TM-650 2.4.8 is greater than or equal to 3.30 lb / in, such as between 3.30 lb / in and 3.70 lb / in;
[0151] The amount of glue flow in the product (e.g., a sample of glue flow in the board) after lamination is greater than or equal to 5.0 mm, for example, between 5.0 mm and 12.0 mm;
[0152] The surface of the product (e.g., a copper-free substrate) does not contain board edge stripes upon visual observation;
[0153] The dielectric constant measured at a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 3.65, for example, between 3.20 and 3.65;
[0154] The dielectric loss measured at a frequency of 10 GHz with reference to the method described in JIS C2565 is less than or equal to 0.0053, for example, between 0.0035 and 0.0053; and
[0155] The flame retardancy measured by the method described in reference to UL 94 specification was V-0 grade.
[0156] The resin compositions of the embodiments of the present invention and the comparative examples of the present invention were prepared using various raw materials from the following sources according to the amounts in Tables 1 to 5, and were further made into various test samples or articles. The compositions and test results of the resin compositions of the embodiments and the comparative examples are shown in Tables 1 to 5 (all in parts by weight).
[0157] SA9000: terminal dimethacrylate polyphenylene ether resin, purchased from Sabic.
[0158] OPE-2st 2200: terminal bisvinylbenzyl polyphenylene ether resin, purchased from Sabic.
[0159] BMI-70: aromatic bismaleimide resin, purchased from KI Chemicals.
[0160] BMI-2300: Benzyl maleimide polymer resin, purchased from Yamato Chemical Industry Co., Ltd.
[0161] BMI-80: aromatic bismaleimide resin, purchased from KI Chemicals.
[0162] TAIC: triallyl isocyanurate, purchased from Qinyu Co., Ltd.
[0163] B-3000: 1,2-polybutadiene resin, purchased from Japan Soda.
[0164] Ricon184MA6: styrene-butadiene-maleic anhydride terpolymer resin, purchased from CRAY VALLEY Company.
[0165] D-1118: styrene-butadiene-styrene terpolymer resin, purchased from KARTON.
[0166] Synthetic compound 1: prepared by the method of Preparation Example 1.
[0167] Synthetic compound 2: prepared by the method of Preparation Example 2.
[0168] Synthetic compound 3: prepared by the method of Preparation Example 3.
[0169] Phosphorus-containing siloxane 1: the substance corresponding to the structure shown in reference formula (IX) when n=1.
[0170] Phosphorus-containing siloxane 2: refers to the substance corresponding to the structure of formula (IX) when 1<n≤10.
[0171] Phosphorus-containing siloxane 3: Refer to the structure of formula (IX), the corresponding substance when n>10.
[0172]
[0173] Vinyl phosphorus-containing siloxane A: as shown in the structure of formula (X):
[0174]
[0175] Vinyl phosphorus-containing siloxane B: as shown in the structure of formula (XI), wherein A is DOPO, B is a benzene ring, and R1, R2, R3, and R4 are phenyl groups:
[0176]
[0177] Phosphorus-containing silane 1: As shown in the structure of formula (XII):
[0178]
[0179] Phosphorus-containing silane 2: As shown in the structure of formula (XIII):
[0180]
[0181] Phosphorus-containing silane coupling agent: as shown in the structure of formula (XIV), wherein X can be selected from isopropyleneoxy.
[0182]
[0183] Phenyltrivinylsilane: purchased from Suzhou Silsuo.
[0184] DOPO: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, purchased from Zhengzhou Alpha Company.
[0185] SC-2500SMJ: spherical silica treated with an acrylate-based silane coupling agent, purchased from Admatechs.
[0186] 25B: 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne peroxide, solid content 100%, purchased from NOF Corporation.
[0187] Butanone: any source
[0188] Toluene: purchased from Qiangdi.
[0189] [Table 1] Composition (unit: weight parts) and property test results of the resin composition of the embodiment
[0190]
[0191] [Table 2] Composition of the resin composition of the embodiment (unit: weight part) and characteristic test results
[0192]
[0193]
[0194] [Table 3] Composition of the resin composition of the embodiment (unit: weight part) and characteristic test results
[0195]
[0196] [Table 4] Composition (unit: weight parts) of comparative resin composition and property test results
[0197]
[0198] [Table 5] Composition (unit: weight parts) of comparative resin composition and property test results
[0199]
[0200]
[0201] The various resin compositions shown in Tables 1 to 5 are used to prepare varnishes and various test objects (samples) in the following manner, and the characteristics are measured according to specific test conditions to obtain test results.
[0202] Varnish
[0203] The components of each embodiment (represented by E, such as E1 to E21) or comparative example (represented by C, such as C1 to C12) are added into a stirring tank according to the dosage in Tables 1 to 5, and stirred. The resin composition formed after uniform mixing is called resin varnish.
[0204] Taking Example E1 as an example, 100 parts by weight of vinyl polyphenylene ether resin (SA9000), 40 parts by weight of aromatic maleimide resin (BMI-70) and 30 parts by weight of synthetic compound 1 (having the structure shown in formula (III)) are added to a stirrer containing an appropriate amount of toluene and an appropriate amount of butanone (the "appropriate amount" of solvent in Tables 1 to 5 represents the amount of solvent used to obtain an ideal solid content of the resin composition, for example, the solid content of the varnish is 65wt%), and stirred until the solid components are dissolved into a liquid homogeneous phase. Then, 140 parts by weight of spherical silica (SC-2500SMJ) are added and stirred until completely dispersed, and then 1 part by weight of a curing accelerator (25B, first dissolved into a solution using an appropriate amount of solvent) is added and stirred for 1 hour to obtain a varnish of the resin composition E1.
[0205] In addition, according to the dosage of the components listed in Tables 1 to 5, the varnishes of other Examples E2 to E21 and Comparative Examples C1 to C12 were prepared by referring to the preparation method of the varnish of Example E1.
[0206] Prepreg (using 2116E-glass fiber cloth)
[0207] The resin compositions of different embodiments (E1 to E21) and comparative examples (C1 to C12) listed in Tables 1 to 5 are added to a stirring tank in batches, mixed evenly and stirred until completely dissolved into varnish, and then the resin compositions are placed in an impregnation tank. Glass fiber cloth (e.g., E-glass fiber cloth with a specification of 2116) is passed through the impregnation tank to make the resin composition adhere to the glass fiber cloth, and heated at 120° C. to 150° C. to a semi-cured state (B-Stage), to obtain a prepreg (resin content of about 52%).
[0208] Prepreg (using 1080E-glass fiber cloth)
[0209] The resin compositions of different embodiments (E1 to E21) and comparative examples (C1 to C12) listed in Tables 1 to 5 are added to a stirring tank in batches, mixed evenly and stirred until completely dissolved into varnish, and then the resin compositions are placed in an impregnation tank. Glass fiber cloth (e.g., E-glass fiber cloth with a specification of 1080) is passed through the impregnation tank to make the resin composition adhere to the glass fiber cloth, and heated at 120° C. to 150° C. to a semi-cured state (B-Stage), to obtain a prepreg (resin content of about 71%).
[0210] Copper foil substrate (made of five prepreg sheets pressed together)
[0211] Prepare two 18 micron thick hyper very low profile 2 copper foils (HVLP2 copper foil) and five prepregs (using 1080E-glass fiber cloth) made from each resin composition in batches. The resin content of each prepreg is about 71%. The copper foil, five prepregs and copper foil are stacked in order, and pressed for 2 hours under vacuum conditions at 220°C to form each copper foil substrate. Among them, the five stacked prepregs will solidify (C-stage) to form an insulating layer between the two copper foils, and the resin content of the insulating layer is about 71%.
[0212] Copper foil substrate (made of eight prepreg sheets pressed together)
[0213] Prepare two 18 micron thick ultra-low profile 2 copper foils (HVLP2 copper foil) and eight prepregs (using 2116E-glass fiber cloth) made from various resin compositions in batches. The resin content of each prepreg is about 52%. The copper foil, eight prepregs and copper foil are stacked in order, and pressed for 2 hours under vacuum conditions at 220°C to form each copper foil substrate. Among them, the eight stacked prepregs will solidify (C-stage) to form an insulating layer between the two copper foils, and the resin content of the insulating layer is about 52%.
[0214] Does not contain copper substrate (made of eight prepreg sheets pressed together)
[0215] The copper foil substrate (formed by laminating eight prepregs) was etched to remove the copper foil on both sides to obtain a copper-free substrate, which was formed by laminating eight prepregs and had a resin content of about 52%.
[0216] Does not contain copper substrate (made of two prepreg sheets pressed together)
[0217] Prepare two 18-micron-thick hyper very low profile 2 copper foils (HVLP2 copper foil) and two prepregs (using 1080E-glass fiber cloth) made from each resin composition in batches. The resin content of each prepreg is about 71%. The copper foil, two prepregs and copper foil are stacked in order, and pressed for 2 hours under vacuum conditions at 220°C to form each copper foil substrate, and then the copper foil on both sides of the copper foil substrate is etched away to obtain a copper-free substrate. Among them, the two stacked prepregs will solidify (C-stage) to form an insulating layer between the two copper foils, and the resin content of the insulating layer is about 71%.
[0218] The test methods and their characteristic analysis items are described as follows.
[0219] 1. Ratio of thermal expansion
[0220] In the measurement of thermal expansion rate (or dimensional change rate), a copper-free substrate (made of eight prepreg sheets pressed together) was selected as the sample to be tested for thermal mechanical analysis (TMA). The sample was heated at a temperature rise rate of 10°C per minute, from 35°C to 265°C, and the Z-axis dimensional change rate of each sample to be tested (50°C to 260°C temperature range, unit: %) was measured with reference to the method described in IPC-TM-650 2.4.24.5. The lower the dimensional change rate percentage, the better.
[0221] Generally speaking, a high Z-axis thermal expansion rate of a substrate indicates a large dimensional change rate. For copper foil substrates, a large dimensional change rate can easily lead to reliability issues such as printed circuit board explosion during processing. In this field, the lower the percentage of thermal expansion rate, the better, and a thermal expansion rate difference greater than or equal to 0.1% is considered a significant difference.
[0222] For example, the Z-axis thermal expansion coefficient of the article made of the resin composition disclosed in the present invention measured by the method described in IPC-TM-6502.4.24.5 is less than or equal to 2.60%, for example, less than or equal to 1.95%, 2.10%, 2.20%, 2.30%, 2.32%, 2.41%, 2.43%, 2.45%, 2.50%, 2.51%, 2.55% or 2.60%, for example, between 1.95% and 2.60%.
[0223] 2. Copper foil tensile strength (also known as peel strength, peel strength, P / S)
[0224] The copper foil substrate (made of eight prepreg sheets pressed together) was cut into rectangular samples with a width of 24mm and a length greater than 60mm, and the surface copper foil was etched, leaving only a long strip of copper foil with a width of 3.18mm and a length greater than 60mm. Using a universal tensile strength tester, the force (lb / in) required to pull the copper foil away from the substrate surface was measured at room temperature (about 25°C) according to the method described in IPC-TM-6502.4.8. The higher the copper foil tensile force, the better, and the difference in copper foil tensile force values greater than or equal to 0.1lb / in is considered significant.
[0225] For example, the copper foil tensile force of the article made of the resin composition disclosed in the present invention measured by the method described in IPC-TM-6502.4.8 is greater than or equal to 3.30 lb / in, preferably greater than or equal to 3.30 lb / in, 3.32 lb / in, 3.40 lb / in, 3.45 lb / in, 3.48 lb / in, 3.50 lb / in, 3.51 lb / in, 3.52 lb / in, 3.55 lb / in, 3.60 lb / in, 3.65 lb / in or 3.70 lb / in, for example, between 3.30 lb / in and 3.70 lb / in.
[0226] 3. Glue flow inside the board
[0227] First, a copper-containing substrate of EM-827 is prepared as a copper-containing core board (available from Zhongshan Taiguang Electronic Materials Co., Ltd., which uses 7628E-glass fiber cloth and 1 ounce HTE copper foil), and the thickness of the copper-containing core board is 28 mils. The surface copper foil of the copper-containing core board is treated by a known browning process to obtain a browning core board.
[0228] Prepare in batches a prepreg obtained from the aforementioned embodiments (E1 to E21) and comparative examples (C1 to C12) (made using 1080E-glass fiber cloth, each prepreg having a resin content of about 71%, a thickness of about 4.5 mils, and a length and width of 17 inches and 15 inches respectively), and the aforementioned brown core board having a thickness of 28 mils and a length and width of 18 inches and 16 inches respectively, wherein the center of the prepreg has a diamond-shaped opening with a length and width of 4 inches (a 4-inch*4-inch diamond-shaped space is punched out in the center of the prepreg using a known punching machine).
[0229] A 0.5 ounce HTE copper foil (reverse pressure, i.e., the bright surface of the copper foil contacts the semi-cured sheet), a semi-cured sheet, and a brown core board are stacked in sequence, and then pressed and cured for 2 hours under vacuum, high temperature (200°C) and high pressure (360psi) conditions to obtain a copper-containing multilayer board. After removing the reverse pressure copper foil on the surface of the copper-containing multilayer board, an in-board glue flow sample can be obtained. Take the in-board glue flow sample, use each side of the 4-inch * 4-inch diamond as the baseline, and divide each side into 4 equal parts with 3 bisection points. Measure the glue flow amount at each of the 12 points (i.e., the vertical glue flow distance at each of the 12 points), and calculate the average value of the glue flow amount at the 12 points to obtain the in-board glue flow amount (average value), in mm. Generally speaking, the in-board glue flow is preferably between 5mm and 12mm.
[0230] 4. Board edge stripes
[0231] The copper foil on both sides of the copper foil substrate (made of five semi-cured sheets pressed together) is etched away to obtain a copper-free substrate. The surface condition of the insulating layer of the copper-free substrate is visually observed by personnel. If a dendritic distribution appears on the edge of the board, it means that the compatibility of the resin composition is poor or the fluidity difference is large, resulting in unevenness. The dendritic distribution of the substrate will cause uneven characteristics of the subsequent circuit board (poor reliability) and a significant reduction in the yield rate, such as poor dielectric properties, low heat resistance, uneven thermal expansion, or poor interlayer bonding. The schematic diagram of the copper-free substrate with dendritic distribution is shown in the figure below. Figure 2 , a schematic diagram of a copper-free substrate with no dendritic distribution is shown in Figure 3 .
[0232] 5. Dielectric constant (Dk) and dielectric loss factor (Df)
[0233] In the measurement of dielectric constant and dielectric loss, the above-mentioned copper-free substrate (made of two prepregs pressed together) was selected as the sample to be tested, and a microwave dielectric analyzer (microwave dielectrometer, purchased from AET, Japan) was used to measure each sample at a frequency of 10 GHz according to the method described in JIS C2565. The lower the dielectric constant or the lower the dielectric loss, the better the dielectric properties of the sample to be tested.
[0234] At a measurement frequency of 10 GHz, when the Dk value is less than or equal to 3.60 and the Df value is less than or equal to 0.005, a difference in Dk values greater than or equal to 0.05 indicates that there is a significant difference between the dielectric constants of different substrates (there is a significant technical difficulty), a difference in Dk values less than 0.05 indicates that there is no significant difference in the dielectric constants of the substrates, a difference in Df values less than 0.0001 indicates that there is no significant difference in the dielectric loss of the substrates, and a difference in Df values greater than or equal to 0.0001 indicates that there is a significant difference between the dielectric loss of different substrates (there is a significant technical difficulty). When the Df value is greater than 0.005, a difference in Df values less than 0.0003 indicates that there is no significant difference in the dielectric loss of the substrates, and a difference in Df values greater than or equal to 0.0003 indicates that there is a significant difference between the dielectric loss of different substrates (there is a significant technical difficulty).
[0235] For example, the article made of the resin composition disclosed in the present invention has a dielectric constant less than or equal to 3.65, such as between 3.20 and 3.65, and a dielectric loss less than or equal to 0.0053, such as between 0.0035 and 0.0053, measured at a frequency of 10 GHz according to the method described in JIS C2565.
[0236] 6. Flame retardancy
[0237] In the flame retardancy test, a copper-free substrate (made of eight prepregs pressed together) was selected as the sample to be tested. The measurement was carried out according to the method described in the UL94 specification, and the flame retardancy analysis results were expressed in V-0, V-1, and V-2 grades, where V-0 is better than V-1, and V-1 is better than V-2.
[0238] For example, the flame retardancy of the article made of the resin composition disclosed in the present invention is measured according to the method described in UL 94 specification and is V-0. In addition, according to the above test results, it can be confirmed that the phosphorus-containing silane compound provided by the present invention can achieve a flame retardant effect of V-0 as a flame retardant.
[0239] The phosphorus-containing silane compound provided by the present invention is different from the existing flame retardant compounds in terms of structure and properties. For example, by comparing the phosphorus-containing silane compound of the structure shown in formula (III) with the vinyl phosphorus-containing siloxane A of the structure shown in formula (X), the vinyl phosphorus-containing siloxane B of the structure shown in formula (XI), and the phosphorus-containing silane coupling agent of the structure shown in formula (XIV), it can be found that the phosphorus-containing silane compound of the structure shown in formula (III) of the present invention contains only one silicon atom in its structure, the silicon atom has a vinyl group and is connected to a phenyl group, and does not contain a silicon-oxygen bond in its structure.
[0240] By comparing Example E3 and Comparative Examples C4, C5 and C8 side by side, it was found that the phosphorus-containing silane compound of the present invention, compared with the vinyl phosphorus-containing siloxane A shown in the structure of formula (X), the vinyl phosphorus-containing siloxane B shown in the structure of formula (XI) and the phosphorus-containing silane coupling agent shown in the structure of formula (XIV), the articles prepared by the phosphorus-containing silane compound have been significantly improved in terms of Z-axis thermal expansion coefficient, board edge stripes, dielectric constant and dielectric loss.
[0241] In addition, by comparing the reactive phosphorus-containing silane compound of the present invention with the non-reactive phosphorus-containing silane 1 represented by the structure of formula (XII) or the phosphorus-containing silane 2 represented by the structure of formula (XIII), it can be found that the phosphorus-containing silane compound of the present invention has one or two vinyl groups attached to the silicon atom.
[0242] By comparing Examples E3 to E5 and Comparative Examples C6 and C7 side by side, it was found that the phosphorus-containing silane compound of the present invention, compared with the non-reactive phosphorus-containing silane 1 represented by the structure of formula (XII) or the phosphorus-containing silane 2 represented by the structure of formula (XIII), not only has good solubility (phosphorus-containing silane 1 and phosphorus-containing silane 2 have the problem of poor solubility), but the prepared articles also have obvious improvements in terms of glue flow within the board and stripes on the edge of the board.
[0243] In addition, by comparing the reactive phosphorus-containing silane compound of the present invention with the non-reactive phosphorus-containing siloxane compound structure shown in the formula (IX), it is found that the phosphorus-containing silane compound of the present invention contains only one silicon atom, the silicon atom is connected to one or two vinyl groups, and the structure does not contain a silicon-oxygen bond.
[0244] By comparing Examples E3 to E5 and Comparative Examples C1 to C3 side by side, it was found that the phosphorus-containing silane compound of the present invention, compared with the non-reactive phosphorus-containing siloxane compound represented by the structure of formula (IX), the articles prepared by the phosphorus-containing silane compound have been significantly improved in terms of Z-axis thermal expansion coefficient, copper foil tensile force, glue flow in the board, board edge stripes, dielectric constant and dielectric loss.
[0245] In addition, the phosphorus-containing silane compound of the present invention is compared with its raw materials phenyltrivinylsilane and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) side by side, such as Comparative Examples C9 to C11. It can be found that the articles made from the phosphorus-containing silane compound of the present invention have improved one, multiple or all of the properties such as Z-axis thermal expansion coefficient, copper foil tensile force, board internal glue flow, board edge stripes, dielectric constant, dielectric loss and flame retardancy.
[0246] By comparing all the embodiments E1 to E21 of the present invention with all the comparative examples C1 to C12, it can be confirmed that the substrates prepared by using the technical solution of the phosphorus-containing silane compound of the present invention can simultaneously achieve one, multiple or all of the technical effects of a Z-axis thermal expansion coefficient of less than or equal to 2.60%, a glue flow amount within the board of greater than or equal to 5.0 mm, and no board edge stripes. On the contrary, comparative examples C1 to C12 that do not use the technical solution of the present invention cannot achieve the aforementioned technical effects.
[0247] The above embodiments are essentially only for auxiliary explanation and are not intended to limit the embodiments of the subject matter of the application or the application or use of these embodiments. In this article, the term "exemplary" means "as an example, example or illustration". Any exemplary embodiment in this article is not necessarily interpreted as being preferred or more advantageous than other embodiments.
[0248] In addition, although at least one exemplary embodiment or comparative example has been proposed in the aforementioned embodiment, it should be understood that the present invention can still have a large number of changes. It should also be understood that the embodiments described herein are not intended to limit the scope, use or configuration of the requested application subject matter in any way. On the contrary, the aforementioned embodiment will provide a simple guide for those skilled in the art to implement one or more of the embodiments described. Furthermore, various changes can be made to the function and arrangement of the elements without departing from the scope defined by the claims, and the claims include known equivalents and all foreseeable equivalents when the present patent application is filed.
Claims
1. A phosphorus-containing silane compound, characterized in that With SiR1(R2) n (R3) 3-n structure: Wherein R1 is phenyl, R2 is vinyl, R3 is independently a structure represented by formula (I) or formula (II), and n is equal to 1 or 2.
2. The phosphorus-containing silane compound according to claim 1, characterized in that Having any one of the structures shown in the following formula (III) to formula (VI):
3. A method for producing a phosphorus-containing silane compound as claimed in claim 1, characterized in that: The method comprises the steps of reacting phenyltrivinylsilane with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide at a temperature of 160° C. to 200° C., wherein no solvent and initiator are added in the reaction.
4. The manufacturing method according to claim 3, characterized in that: The molar ratio of phenyltrivinylsilane to the reactive functional group of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or diphenylphosphine oxide is between 3:1 and 3:
2.
5. A resin composition, characterized in that The invention comprises the phosphorus-containing silane compound as claimed in claim 1 and a resin additive.
6. The resin composition according to claim 5, characterized in that The resin additive includes vinyl resin, styrene maleic anhydride resin, epoxy resin, phenol resin, benzoxazine resin, cyanate resin, polyester resin, polyamide resin, polyimide resin or a combination thereof.
7. The resin composition according to claim 6, characterized in that The vinyl-containing resin includes vinyl-containing polyphenylene ether resin, maleimide resin, maleimide triazine resin, polyolefin resin, styrene, divinylbenzene, di(vinylbenzyl)ether, 1,2,4-trivinylcyclohexane, di(vinylphenyl)ethane, di(vinylphenyl)hexane, divinylphenyl dimethylene ether, divinylphenyl dimethylene benzene, triallyl isocyanurate, triallyl cyanurate, a prepolymer of any of the foregoing components, or a combination thereof.
8. The resin composition according to claim 7, characterized in that The vinyl-containing polyphenylene ether resin includes a terminal vinyl benzyl polyphenylene ether resin, a terminal methacrylate polyphenylene ether resin or a combination thereof.
9. The resin composition according to claim 8, characterized in that The terminal vinyl benzyl polyphenylene ether resin and the terminal methacrylate polyphenylene ether resin respectively include structures represented by formula (VII) and formula (VIII): Among them, R1 to R 14 Each is independently H or -CH3, W1 and W2 are each independently a C1 to C3 divalent aliphatic group; b1 is an integer from 0 to 8; Q1 includes any one or a combination of the structures shown in formula (B-1) to formula (B-3): Y1 and Y2 each independently comprise a structure represented by formula (B-4): Among them, R 15 To R 30 Each is independently H or -CH3; m1 and n1 are each independently an integer from 1 to 30; and A1 is selected from a covalent bond, -CH2-, -CH(CH3)-, -C(CH3)2-, -O-, -S-, -SO2- and a carbonyl group.
10. The resin composition according to claim 7, characterized in that The maleimide resin includes 4,4'-diphenylmethane bismaleimide, phenylmethane maleimide oligomer, m-phenylene bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, 2,3-dimethylbenzene maleimide, 2,6-dimethylbenzene maleimide, N-phenyl maleimide, maleimide resin containing aliphatic long chain structure or a combination thereof.
11. The resin composition according to claim 7, characterized in that Compared to 100 parts by weight of the vinyl-containing polyphenylene ether resin, the content of the maleimide resin is 10 parts by weight to 60 parts by weight, and the content of the phosphorus-containing silane compound is 30 parts by weight to 70 parts by weight.
12. The resin composition according to claim 5, characterized in that It further includes an amine curing agent, a flame retardant, an inorganic filler, a curing accelerator, an inhibitor, a dye, a solvent, a toughening agent, a silane coupling agent or a combination thereof.
13. An article made of the resin composition according to claim 5, comprising a prepreg, a resin film, a laminate or a printed circuit board.
14. The article according to claim 13, characterized in that Its surface is free of plate edge streaks upon visual observation.
15. The article of claim 13, wherein: The amount of glue flow in the plate of the article after lamination is greater than or equal to 5.0 mm.
16. The article of claim 13, wherein: The Z-axis thermal expansion rate measured according to the method described in reference to IPC-TM-650 2.4.24.5 is less than or equal to 2.60%.
Citation Information
Patent Citations
Polyphenylene oxide resin, method of preparing polyphenylene oxide resin, polyphenylene oxide prepolymer and resin composition
US20160185904A1
Phosphoric organic silicon compound, preparation method and application thereof
CN101445520A
Resin composition and article made therefrom
CN112646463A